The ecology and culture of the rock catlet Chiloglanis pretoriae (Pisces : mochokidae) - De Villiers, Pierre (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1991)
Chiloglanis pretoriae is a rock catlet, indigenous to southern Africa. The aim of the study was to develop a technique to culture C. pretoriae as an alternative to harvesting and selling wild caught fish on the international aquarium trade. As nothing was known about the culture of African rock catlets an investigation into the biology and ecology of the species was necessary to develop the culture protocol. Chiloglanis pretoriae inhabits fast flowing rapids (current speeds over 0.6 metres per second). It is a serial interstitial gravel spawner, that spawns during the summer months. Chiloglanis pretoriae is a carnivorous fish species, feeding on aquatic insects. The natural growth rate is relatively fast in the first two years where after it levels off. Sexual maturity (50%) is attained within the first year (44mm total length). From the four cell stage, embryos took seven days to hatch, 16 days to first feeding and 75 days to reach the juvenile phase. The free embryos were well developed and readily accepted artificial feed at first feeding. The fish spawned readily, without hormone induction, in a continuous raceway. Spawning in the 801 retangular glass aquaria was irregular. The substrate within the raceway consisted of gravel and large rocks. The current was maintained at 0.6m/sec, temperature at 26Â± 0.6â °C, dissolved oxygen concentrations at 7.1Â± 0.3mg/l, pH at 6.9Â± 0.2 and photoperiod at 16L:8D. Conductivity was monitored and remained within the acceptable range of C. pretoriae (84Â± 10uS/m).
Keywords: Catfishes -- Africa; Catfishes -- Breeding -- Africa; Catfishes -- Ecology -- Africa; Fishes -- Cultural control -- Africa; Fishes -- Cultural control